UPLC-ESI-MS/MS Analysis and Evaluation of Antioxidant Activity of Total Flavonoid Extract from Paeonia lactiflora Seed Peel and Optimization by Response Surface Methodology (RSM). - Shi, Guiqin; Shen, Jiaxin; Wei, Tao; Ren, Fei; Guo, Famou; Zhou, Yuan (BioMed Research International, 2021)
In this study, the ultrasound-assisted extraction (UAE) of flavonoid from Paeonia lactiflora seed peel was optimized by response surface methodology (RSM). Single-factor experiments and a three-factor three-level Box-Behnken design (BBD) were performed to explore the effects of the following parameters on flavonoid extraction: ethanol concentration ( X 1 ), liquid-solid ratio ( X 2 ), and ultrasonic time ( X 3 ). The results showed that the optimal flavonoid yield (10.9045 mg RE/g) was as follows: ethanol concentration 62.93%, ultrasonic time 64.56 min, and liquid-solid ratio 24.86 mL/g. The optimized extract of P. lactiflora seed shell was further analyzed by UPLC-ESI-MS/MS, and 20 main flavonoids were identified and quantified, among which protocatechuic acid, vanillic acid, 4-hydroxybenzoic acid, and 3,4-dihydroxybenzaldehyde had the highest content. Furthermore, the results of the antioxidant test showed that the P. lactiflora seed peel extract obtained under optimized UAE conditions exhibited good antioxidant activity. The experimental results showed that ultrasound-assisted extraction was a fast, efficient, and simple method for extracting active ingredients from P. lactiflora seed peel, thereby making this byproduct a promising source of compounds in food and healthcare sectors.